Eficacia del ciclo de esterilización en autoclaves, centros de salud Riobamba, 2019 - Jenny Paola, Defáz Torres (2021)
ABSTRACT This research analyzes the effectiveness of the sterilization cycle in autoclaves in health centers in the city of Riobamba. It had a qualitative, descriptive, observational, cross-sectional cohort approach, in which 6 autoclaves were evaluated with loads of 0%, 25%, 50%, 75% and 100%, in the dental service units; Three autoclaves at the General Teaching Hospital of Riobamba, one autoclave at the Alfonso Villagómez Pediatric Hospital, one autoclave at the Santa Rosa Health Center and one autoclave at the Calpi Health Center, using the biological indicators in different locations within the equipment (front, center and back) for each load. According to the results obtained, the biological indicators used in the processes without load (0%) and with a load of 25%, in front, middle and back positions were effective in all the sub-centers evaluated, however, the results with loads of 50%, 75% and 100% located in front, middle and back of the equipment showed deficiencies with ineffective markers in the sub-centers some sub-centers with the exception of sub-center 3 (Santa Rosa Health Center) in which the sterilization process was effective in all the loads and sites where the biological indicators were located. It is concluded that the effective loads are evidenced in all the positions in values no greater than 25%. Keywords: Autoclave, sterilization, dentistry, biological indicators, sanitary devices.